Prevalence and associated factors of depression among breast cancer patients in Sub-Saharan Africa: A systematic review and meta-analysis - Anissa Mohammed; Dagnachew Melak; Fekade Demeke Bayou; Husniya Yasin; Aregash Abebayehu Zerga; Birhanu Wagaye; Fanos Yeshanew Ayele; Ahmed Hussien Asfaw; Natnael Kebede; Asnakew Molla Mekonen; Mengistu Mera Mihiretu; Yawkal Tsega; et al. (SAGE Open Medicine, 2024)
Introduction: Even though breast cancer incidence is lower in Sub-Saharan Africa, its mortality is higher in these countries. However, the impact does not end with diagnosis and treatment; rather many patients struggle with depression which is very common among these patients. This systematic review and meta-analysis helps to provide valuable insights into the overall prevalence of depression and associated factors among breast cancer patients in Sub-Saharan Africa. Method: We searched several databases, including MEDLINE, Embase, Scopus, Hinary, CINHAL and Google Scholar to retrieve relevant literatures from inception up to 15 June 2023. All observational studies, published in English at any time were included, while, letters to editor, review articles, commentaries, interventional and qualitative studies, and, abstracts presented in conferences or seminars were excluded. The results of this systematic review and meta-analysis have been written based on the PRISMA 2020 checklist and the protocol have been registered in PROSPERO database (CRD42023428910). Result: We have included nine articles with 2226 study participants. The result showed that, the pooled prevalence of depression among breast cancer patients in Sub-Saharan Africa was 45.6% (95% CI: 30%–61%) with significant heterogeneity I 2  = 98.9%, (Cochrane) Q  < 0.0001. There was no single study effect and publication bias but substantial heterogeneity was observed. In addition, there has been a publication bias with eggers test ( p  < 0.0033). However, there were no studies imputed after trim and fill analysis. From the factors, breast cancer patients who had poor financial support were 1.47 (95% CI: 1.02–2.13) times more at risk of developing depression than their counterparts. Conclusion: The prevalence of depression among breast cancer patients in Sub-Saharan Africa countries were higher than other regions. Thus, Emphasis should be given on developing financial assistance programs designed to cover the medical costs and improving the health care infrastructure.